2008
DOI: 10.1186/1755-8794-1-14
|View full text |Cite
|
Sign up to set email alerts
|

The role of the small intestine in the development of dietary fat-induced obesity and insulin resistance in C57BL/6J mice

Abstract: Background: Obesity and insulin resistance are two major risk factors underlying the metabolic syndrome. The development of these metabolic disorders is frequently studied, but mainly in liver, skeletal muscle, and adipose tissue. To gain more insight in the role of the small intestine in development of obesity and insulin resistance, dietary fat-induced differential gene expression was determined along the longitudinal axis of small intestines of C57BL/6J mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
140
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(160 citation statements)
references
References 51 publications
18
140
2
Order By: Relevance
“…One of these genes ( Reg3g , Fig. 4D ) was previously shown to have decreased expression on a high-fat diet in wild-type C57BL/6J mice ( 26,27 ). The data in Fig.…”
Section: Feeding Wd To Ldlrmentioning
confidence: 68%
See 3 more Smart Citations
“…One of these genes ( Reg3g , Fig. 4D ) was previously shown to have decreased expression on a high-fat diet in wild-type C57BL/6J mice ( 26,27 ). The data in Fig.…”
Section: Feeding Wd To Ldlrmentioning
confidence: 68%
“…The 64 genes ( Tables 2, 4 ) are involved in several pathways including peroxisome proliferatoractivated receptor (PPAR) signaling, lipid and cholesterol metabolism, mitochondrial function, and oxidative stress ( Tables 3, 5 ). Among these 64 genes were seven genes that were identifi ed by others as showing increased expression in the small intestine of C57BL/6J mice on a highfat diet ( 26,27 ), and confi rmed by us on feeding WD compared with chow in LDLR Ϫ / Ϫ mice on a C567BL/6J background ( Table 4 ). These genes were Acadl , Acot1 , Angptl4 , Acaa1b , Cyp4a10 , Scd1 , and Srebf1 .…”
Section: Feeding Wd To Ldlrmentioning
confidence: 76%
See 2 more Smart Citations
“…They found that the biological processes influenced by feeding a high-fat diet were related to lipid metabolism, cell-cycle regulation and inflammation/immune response. For this last process, they could not draw a definitive conclusion on inflammatory status of the small intestine as a whole, because almost no gene showed a consistent up-or down-regulation in all the segments of the small intestine (de Wit et al 2008). In the study conducted by Ding and co-workers, C57BL/6 mice were exposed to high-fat or low-fat diets and assessed for the expression of multiple pro-inflammatory cytokines in the small intestine and in the colon.…”
Section: Introductionmentioning
confidence: 99%